2013
DOI: 10.1128/aac.00488-13
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Glyceryl Trinitrate as an Effective Adjunctive Treatment with Artemether for Late-Stage Experimental Cerebral Malaria

Abstract: c Cerebral malaria (CM) is associated with low nitric oxide (NO) bioavailability, cerebrovascular constriction, occlusion, and hypoperfusion. Administration of exogenous NO partially prevents the neurological syndrome and associated vascular pathology in an experimental CM (ECM) mouse model. In this study, we evaluated the effects of transdermal glyceryl trinitrate in preventing ECM and, in combination with artemether, rescuing late-stage ECM mice from mortality. The glyceryl trinitrate and/or artemether effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…Adjunctive treatment with the vasodilators nimodipine and glyceryl trinitrate improves survival in ECM mice. 12,14,38,39 As ET-1 is a potent vasoconstrictor, 40 we used intravital microscopy in mice implanted with chronic cranial windows to analyze the brain microvascular changes caused by the ET-1 during experimental malarial infection. PbA-infected mice and PbNinfected ET-1etreated mice displayed significant degrees of brain arteriolar constriction at 5 and 6 dpi ( Figure 5, A and B).…”
Section: Et-1 Treatment Causes Brain Arteriolar Constriction and Decrmentioning
confidence: 99%
“…Adjunctive treatment with the vasodilators nimodipine and glyceryl trinitrate improves survival in ECM mice. 12,14,38,39 As ET-1 is a potent vasoconstrictor, 40 we used intravital microscopy in mice implanted with chronic cranial windows to analyze the brain microvascular changes caused by the ET-1 during experimental malarial infection. PbA-infected mice and PbNinfected ET-1etreated mice displayed significant degrees of brain arteriolar constriction at 5 and 6 dpi ( Figure 5, A and B).…”
Section: Et-1 Treatment Causes Brain Arteriolar Constriction and Decrmentioning
confidence: 99%
“…10,11 We have also shown that administration of exogenous NO improves cerebral microcirculatory physiology in P. berghei infected mice 1315 and that glyceryl trinitrate, a drug that generates NO, reverses cerebrovascular constriction and improves survival in mice with ECM. 16 Artemisinin derivatives are potent, fast-acting antimalarial drugs, and intravenous artesunate is the mainstay treatment for human cerebral malaria. 2 We hypothesized that the combination of artemisinin with NO-donors would bring together the potent antimalarial activity of the former with the vascular benefit of the latter and therefore be a more efficacious drug for treating cerebral malaria.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…12 Administration of NO donors can prevent the neurological syndrome and the associated vascular dysfunction, 1315 and more important, NO donors such as glyceryl trinitrate improve survival of mice with late-stage ECM and reverse ECM cerebrovascular constriction. 16 In a previous study we designed a new series of hybrid compounds in which amodiaquine, an established antimalarial drug included in the World Health Organization Model List of Essential Medicines, 17 was joined with NO-donor furoxan and nitrooxy (ONO 2 ) 18 moieties and studied them as potential anti SM/CM tools. All the amodiaquine-NO-donor hybrids were able to dilate rat aorta strips precontracted with phenylephrine with a NO-dependent mechanism and displayed high degree of activity against both chloroquine-sensitive and chloroquine-resistant strains of P. falciparum .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Treatment with S-nitrosylated glutathione (GSNO), an endogenous, physiological NO donor, prevented ECM development while having milder effects on blood pressure (71). Glyceryl trinitrate (nitroglycerin; GTN) not only prevented ECM but also worked as adjunctive therapy with artemether, markedly increasing survival of mice with late-stage ECM compared to artemether alone (72). The benefit in survival was associated with reversal of cerebrovascular constriction, suggesting that the effect was due to improved brain perfusion.…”
Section: Nitric Oxidementioning
confidence: 99%